KUALITAS PELAYANAN PENGADUAN PELANGGAN PDAM DI KECAMATAN PONTIANAK BARAT - Ferry Irawan E.21109055 (FISIP Universitas Tanjungpura, 2013)
This paper is motivated by the inaction in following customer complaints. Writing focus on quality customer service complaints with aspects include: reliability, responsiveness and empathy. The reliability or the ability of employees to provide service to the customer complaints, including complaints certainty of service time, is the lack of certainty of time to follow-up of complaints, and there is no explanation or information about the certainty of the waiting time for complaint. Employee owned responsiveness is quite good, although there are some employees who are less communicative in explaining or in response to customer inquiries. Empathy or concern for customer complaints, as reflected in employee attitudes in dealing with customer complaints is not the establishment of an interactive communication between the employee service providers with the customer complaints as a customer. Keywords: Quality of Service, Customer Complaints.